2016
DOI: 10.1161/jaha.116.003782
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Language Preference and Intravenous Thrombolysis Among Acute Ischemic Stroke Patients

Abstract: BackgroundApproximately 20% of the US population primarily speaks a language other than English at home. Yet the effect of language preference on treatment of acute ischemic stroke (AIS) patients remains unknown. We aimed to evaluate the influence of language preference on AIS patients’ receipt of intravenous (IV) thrombolysis.Methods and ResultsWe analyzed data from 3894 AIS patients who participated in the American Heart Association “Get With The Guidelines®—Stroke” program at our hospital from January 1, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…We previously reported that 9.3% of AIS patients cared for at our institution were NEP and that they were more likely than English-speaking patients to self-identify as racial/ethnic minorities, to be uninsured or have Medicaid, and to live in neighborhoods with higher poverty levels. 8 Several potential barriers may have affected NEP AIS patients who did not receive PMI services despite our institutional policies and systems to facilitate PMI use. Treating clinicians may have perceived a lack of available PMIs, experienced time constraints, or preferred to communicate through other means including ad hoc interpretation by patients' family members or other hospital staff.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously reported that 9.3% of AIS patients cared for at our institution were NEP and that they were more likely than English-speaking patients to self-identify as racial/ethnic minorities, to be uninsured or have Medicaid, and to live in neighborhoods with higher poverty levels. 8 Several potential barriers may have affected NEP AIS patients who did not receive PMI services despite our institutional policies and systems to facilitate PMI use. Treating clinicians may have perceived a lack of available PMIs, experienced time constraints, or preferred to communicate through other means including ad hoc interpretation by patients' family members or other hospital staff.…”
Section: Discussionmentioning
confidence: 99%
“…As we described previously, GWTG‐Stroke is a national data collection system and performance measurement tool developed by the American Heart Association to improve the quality of care and outcomes for patients with stroke and transient ischemic attack 8. Our institution is a 999‐bed hospital in Boston, MA, with longstanding efforts to provide quality stroke care per nationally accepted standards and recommendations.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations